The greenprint : plant-based diet, best body, better world - Borges, Marco (Harmony Books, 2018)
Accessible and easy-to-follow, The Greenprint is a movement to embrace your absolute best and healthiest life. Through his more than two decades of experience working with clients, including some of the world's biggest celebrities, and spearheading exercise and nutrition research, Borges developed the groundbreaking "22 Laws of Plants," which he's determined are the most important plant-based diet, exercise, and lifestyle secrets for losing weight, increasing energy, boosting metabolism, and reducing inflammation, not to mention helping minimize your carbon imprint to help the planet. The Greenprint outlines three simple, step-by-step plans to implement the 22 Laws into your life, depending on where you are on your journey. Whether you are ready for a gradual shift or excited to tackle them all full-on, in just weeks you will be on your way to a healthier, cleaner approach to eating that includes plenty of whole grains, bountiful veggies, legumes, nuts and more. You'll also find meal plans, more than 60 delicious recipes, countless tips, and inspirational stories to help you along the way. Take control of your diet, create your own Greenprint and forever alter your weight, your health and the planet.--